Owners’ signs of magazine «Vestnik Evropy» as a source on the history of Belarusian libraries in the XIX - early XX centuries - E. P. Denisenko (Библиосфера, 2018)
The article reviews attributed owners’ signs of Belarusian libraries (public, private and specialized) on pages of the monthly magazine «Vestnik Evropy» (1866-1918) (issued in the XIX - early XX centuries). The analysis of the magazine circulation at the territory of modern Belarus provides copious data for the further research in the field of bibliology, historiography and art history.